Moisture transport between the South Atlantic Ocean and southern Africa: relationships to summer rainfall and associated dynamics - (:unkn) unknown (My University, 2008)
Moisture exchange between the South Atlantic and southern Africa is examined in this study through zonal moisture transport. Along the west coast of southern Africa, a multivariate analysis of the zonal flow of moisture computed from NCEP-DOE AMIP II Re-analyses reveals a primary mode of variability typical of variations in intensity and of the latitudinal migration of the circulation associated with the midlatitude westerlies and the South Atlantic anticyclone. In austral summer (January–February), this mode, referred to as the South Atlantic midlatitude mode, is found to be well correlated with rainfall over southern Africa (i.e. to the south of the upper lands surrounding the Congo basin). Its positive/negative phases are found to correspond with surface pressures changes over the South Atlantic region in austral summer when the South Atlantic anticyclone is shifted northward/southward respectively. Such changes are accompanied by dipole-like SST anomalies in the midlatitude South Atlantic Ocean, while simultaneous SST anomalies with a similar structure are also found over South Indian Ocean regions. In January–February, positive/negative events linked to the South Atlantic midlatitude mode are marked by meridional shifts (northward/southward) and weakening/strengthening of the ITCZ over the southern tropics, together with modulations in intensity (weakened/sustained) of the Angola low, which could act as a tropical source of moisture for Tropical Temperate Troughs (TTTs). In association with a strengthened/weakened zonal component of the southern extension of the African Easterly Jet (AEJ), this could modulate the meridional transfer of moisture south of 15°S to the advantage/detriment of Angolan coastal regions, where above/below rainfall are expected. Variations in the latitudinal position (northward/southward) of the South Atlantic anticyclone, and thus of the midlatitude westerlies, are also found to reduce/favour moisture advection toward
Keywords: African Research